A case of familial intracranial calcification – Fahr’s disease - Anu Jacob; George Sarin Zacharia (Muller Journal of Medical Sciences and Research, 2025)
Fahr’s disease, an uncommon disorder characterized by bilateral intracranial brain parenchymal calcification, presents with diverse neurological manifestations. It is often an autosomal dominantly inherited disorder with incomplete penetrance. The most frequently implicated are mutations involving SLC20A2 on chromosome 8p, while others involve genes XPR1, PDGFRB, PDGFB, and IBGC1. Neuroimaging typically reveals symmetrical dense calcifications, predominantly affecting the basal ganglia but may extend to other brain regions. Diagnosis relies on classical imaging findings, exclusion of alternative etiologies, and a positive family history or genetic analysis. This case report describes a patient with dysarthria, choreoathetosis, and spasticity, with CT brain confirming dense bilateral calcification of the basal ganglia, in whom, despite extensive evaluation, no specific etiology was identified, prompting consideration of Fahr’s disease. Neuroimaging of the patient’s son confirmed similar findings, suggesting the familial nature of the disease. Unfortunately, effective therapies to prevent or halt disease progression are lacking, and treatment mainly focuses on managing symptoms.